1999
DOI: 10.1159/000013825
|View full text |Cite
|
Sign up to set email alerts
|

The Binaural Interaction Component in Human ABR Is Stable within the 0- to 1-ms Range of Interaural Time Differences

Abstract: The effect of unilaterally delayed acoustic stimuli on binaural interaction was studied in 12 subjects with normal hearing. Auditory brainstem response (ABR) was obtained in the midline between the forehead and the neck, and click stimuli were unilaterally delayed at 0.2-ms intervals in the 0- to 1-ms range. Binaural interaction was evaluated by measuring the β wave in the binaural difference waveform, i.e. the remainder after subtracting the binaurally evoked registration from the sum of the two monaural regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
26
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 22 publications
14
26
0
6
Order By: Relevance
“…This is in accordance with the studies by Furst et al (1985) and McPherson and Starr (1995). Other studies did not observe any change of the BD amplitude for ITD = þ 0.4 ms: Jones and van der Poel (1990), Brantberg et al (1999b) found a constant DN1 up to ITD = 1 ms. However, the number of sweeps recorded per stimulus condition used in those studies ranged from 4000 to 6400, and in none of them a randomized stimulation paradigm was used.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the studies by Furst et al (1985) and McPherson and Starr (1995). Other studies did not observe any change of the BD amplitude for ITD = þ 0.4 ms: Jones and van der Poel (1990), Brantberg et al (1999b) found a constant DN1 up to ITD = 1 ms. However, the number of sweeps recorded per stimulus condition used in those studies ranged from 4000 to 6400, and in none of them a randomized stimulation paradigm was used.…”
Section: Discussionsupporting
confidence: 92%
“…Tabelle 1), die sich mit dem Einfluss der interauralen Laufzeitdifferenz auf das binaurale Differenzpotenzial beschäftigt haben, beschränken sich bei ihren Untersuchungen lediglich auf die Betrachtung einer einzigen [3,25] oder maximal zweier Potenzialkomponenten [18].…”
Section: Diskussionunclassified
“…Die Werte schwanken zwischen 5,67 ms [18], 6,18 ms [3] und 6,9 ms [25]. Berücksichtigt man, dass Brantberg et al [3] sowie Jones und van der Poel [18] berichten, Welle β bzw. P 1 sei der absteigenden Flanke von Peak V zuzuordnen, so würde dies der von uns identifizierten Welle DN 1 mit einer mittleren Latenz von 5,66 ms entsprechen.…”
Section: Diskussionunclassified
See 2 more Smart Citations